Context Matters Less Than Leadership in Preventing Unethical Behaviour in International Business - Antunez, Marlond (2023)
This study empirically tests a sequential mediation model that links ethical leadership with employees’ unethical behaviour. The corruption index for countries is used as the moderator, because it represents both the instrumental ethical climate and the employee displacement of responsibility embedded in society’s ethical standards. A total of 175 participants comprising 41 teams (134 dyads) across 13 countries participated in a dyadic two-wave survey. The fndings show that ethical leadership has an indirect infuence on the avoidance of unethical behaviour by reducing the instrumental ethical climate and by negating the displacement of individuals’ responsibility. In addition, the results also show that this process is not sensitive to the countries’ corruption levels. Such fndings suggest that organizations are less prone to adjust their ethical standards to the environment than is usually expected. Accordingly, ethical leaders of MNCs may be instrumental in counteracting any corruptive pressure in the social environment, and likewise, non-ethical leaders may be a contributing factor to fostering corrupt organizations in a society that otherwise values ethical principles in business.